The transactional framework of sharecropping: further implications - Chew, Tek‐Ann (John Wiley and Sons Inc, 1993)
In this paper, the transactional framework of sharecropping, recently published, is used to explore various controversies in cropsharing. Conventional sharecropping theories have resulted in a plethora of propositions, making the empirical verification of them confusing. It is difficult to tell which proposition holds for the real world and which holds under perfectly competitive conditions. The transactional framework proposed provides a simple, prosaic underpinning for some of these arguments. Consistent explanations for the main cropsharing issues are possible, using the transactional framework.